ANALISIS PENDAPATAN, RISIKO DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI KARET DI KECAMATAN PAKUAN RATU KABUPATEN WAY KANAN - Rana Cindi Minartha; Fembriarti Erry Prasmatiwi; Adia Nugraha (Lampung University, 2022)
The study aims to analyze the amount of household income, the risk of rubber selling prices and the level of household welfare of rubber farmers in Pakuan Ratu Sub-District, Way Kanan Regency. The research method used was survey method. The number of the respondent in this study is 56 rubber farming households obtained using proportional random sampling. The results show that the average total income of rubber farmer households is Rp31,580,310.71 where the largest income is derived from income from rubber farming. The price risk on rubber farming is relatively small that can be seen from the variation coefficient value (CV) is 0.17. The level of household welfare based on Sajogyo's indicators shows that 100% rubber farming households are in the living groupworthy. Key words: farmers, income, risk, rubber, welfare.